Lateral load behaviour of GFRG infilled RC frame with CFS connection - local and global behaviour - Shaji, Aishwarya; Prasad, A. Meher; Menon, Devdas (Journal of Structural Engineering, 2024)
Glass Fibre Reinforced Gypsum (GFRG) panels can be used as infills in multi-storeyed framed construction, and thelateral load behaviour of GFRG infilled Reinforced Concrete (RC) frames is strongly influenced by the filling inside thecavities of the panel. When the cavities of the panel are left unfilled, the connection between the GFRG panel and theRC frame is established using Cold-Formed Steel (CFS) sections with suitable screw connections. A quasi-static cycliclateral load test was performed on GFRG infilled RC frame with empty cavities to understand their behaviour. Theresults highlighted the significance of the screw connection between the GFRG panel and CFS plate, which experiencesshear, in determining the behaviour of GFRG infilled RC frames. Therefore, the behaviour and strength of the screwconnection between CFS profiles and the GFRG panel was studied by conducting monotonic and cyclic shear loadtests. The results demonstrated the influence of CFS plate thickness, screw diameter, edge distance of the screws andplacement of the CFS plate on various performance parameters of CFS-GFRG screw connection.